Mixing QE and Interest Rate Policies at the Effective Lower Bound: Micro Evidence from the Euro Area - Christian Bittner; Alexander Rodnyansky; Farzad Saidi; Yannick Timmer (Center for Economic Studies and ifo Institute (CESifo), 2021)
In the presence of negative monetary-policy rates and a zero lower bound on deposit rates, banks that are more exposed to central banks' asset-purchase programs reduce their lending to the real economy by more than their counterparts. When banks face a lower bound on customer deposit rates, an asset swap between securities and reserves reduces banks' net worth as the cost of holding reserves cannot be matched with a reduction in their cost of funding. Exploiting euro-area syndicated lending data and the German credit registry, we provide evidence that deposit-reliant banks with relatively higher funding costs and greater exposure to large-scale asset purchases reduce corporate lending relatively more, have lower stock returns, and rebalance their interbank lending from safe to risky countries.
Keywords: E52; E58; G21; 330; negative interest rates; quantitative easing; unconventional monetary policy; bank lending channel